Difficult texts: 1 Corinthians 5.5 – ‘Hand this man over to Satan …’ - Horrell, David G. (Theology, 2020)
First Corinthians 5.5 is ‘difficult’ in two ways, in terms both of understanding its meaning and of its morally questionable instruction. The crucial phrase about handing the offender ‘over to Satan for the destruction of the flesh’ is best seen, following recent research, as a curse, akin to other ancient curse formulae found in Corinth and elsewhere, consigning a person into the hands of a divine being for punishment and death. This makes Paul’s instruction morally difficult and objectionable, but does not prevent us finding other fruitful points of reflection in this text, specifically concerning the way in which the Church, like Paul’s assembly, might locate itself in relation to its wider culture and the norms of that culture.